The Effectiveness of Using Microsoft Office Sway Media on Students' Digital Literacy - Vivi Rulviana; Dian Permatasari Kusuma Dayu; Diyan Marlina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Microsoft office sway is a learning media that is a presentation tool, created and played online. The following research was conducted to know the effectiveness of sway on student digital literacy in online learning after the covid-19 pandemic. This research is quantitative research with a quasi-experimental method. The design used is the Nonequivalent Control Group Design. In this study, the population used was 4th-semester students of the PGSD UNIPMA study program. The sampling technique used in this research is purposive sampling. The sample used in this study was 30 students in the experimental class and 30 in the control class. Furthermore, the instruments used in this study were tests and questionnaires. Test the hypothesis in this study using the t-test. Based on the research activities, it was found that the Microsoft Office Sway media was effective on students' digital literacy. Keywords: Digital Literacy, Microsoft Sway, Online Learning